Biomass Processing Research in Enea CR Trisaia (Italy) and in the Gas Institute of NAS of Ukraine - Sharma, V.K.; Braccio, G.; Freda, C.; Antoshchuk, T.; Pyanykh, K.Ye.; Karp, I.N.; Ilienko, B.K.; Zinoviev, S. (Энерготехнологии и ресурсосбережение, 2012)
The main results of R&D activities on biofuel research area of Biomass laboratory at ENEA CR Trisaia and Combustion Processes Department of the Gas Institute of NAS of Ukraine such as synthesis gas, ethanol and produced gas production for natural gas substitution in industrial steam boilers are represented.